Pengaruh Literasi Keuangan Syariah, Religiusitas, dan Motivasi Investasi Terhadap Minat Investasi di Pasar Modal Syariah (Studi Kasus Muslim di Bogor) - Hidayat, Afra Najla; Diana, Dina (Airlangga Journal of Innovation Management, 2024)
Along with the increasing number of investment transactions which continued to soar until the end of 2023, the Islamic Capital Market is additionally playing its role in improving the economy in Indonesia, especially for Muslims who want to carry out investment transactions within the Sharia corridor. This research aims to find out whether Islamic financial literacy, religiosity, and investment motivation significantly influence on investment intention in the Islamic Capital Market with a case study of Muslims in Bogor. The object is chosen Bogor is one of the largest Muslim regions in West Java, as the province itself is the top ten largest Muslim community in Indonesia. The results of research using SEM-PLS (Structural Equation Model Partial Least Square) show that Islamic financial literacy has no significant effect on investment intention in the Sharia Capital Market as the T-Statistic is being rejected (0.524 > 0.05), but religiosity (0.001 < 0.05) and investment motivation (0.000 < 0.05) are proven to have a significant influence on investment motivation in Sharia Capital Market as the T-Statistics are being accepted. However, this study complements previous research differentiating the research scope and summoning some variables that was used in the previous research. Religiosity is measured by the respondent's consideration of Islamic law in investment institutions, while investment motivation means the respondent's desire to fulfill their physiological needs, sense of safety needs, social needs, esteem needs, and self-actualization needs.